Analisis Perbandingan Penilaian Kualitas Teks Terjemahan Video The Eager Beavers and Old Mr. Oldkool Sebagai Media Pembelajaran Bahasa Inggris - Dina Fitri Annisa (Academica: Journal of Multidisciplinary Studies, 2018)
AbstractAlong with the times, the work of translation is not just limited to books. But also penetrated the learning videos and film subtitles. This research focuses on two translation videos by English Language Education students at IAIN Surakarta. This is considered very important because it is hoped that the video can support English learning to be more easily understood with the presence of English as well as its meaning in Indonesian. This research is a qualitative descriptive study because the data taken comes from the phenomenon of translation of children's texts related to the quality of the translation. video I and video II have different translation qualities, although they are both translated by seventh semester English Language Education students. Video I found that the results of the translation were inaccurate, unacceptable and still difficult to understand so that further analysis was needed to improve the quality. For video II, the results of the translation are accurate, acceptable and easy to understand. It just needs a little improvement on the grammatical part.Keywords: Translation, English Education, video